EVALUASI IMPLEMENTASI NILAI-NILAI ISLAM DALAM PEMBELAJARAN PKN DI SEKOLAH DASAR - Kaulan Karima, Muhammad; Mona Adha, Mohammad; Intan Murni, Cahya; Dewi Egatri, Dewi Egatri; Narhendi, Narhendi; Handayani, Fitri; Rama Dhany, Kenny; Nurhayati, Nurhayati; Pangestu, Yoga (Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to evaluate and analyze the implementation of Islamic values in civic education learning in elementary schools. This study uses a descriptive qualitative research method, the approach used is library research. The results of this study found that the implementation of Islamic values in PKN learning in elementary schools has been implemented, but still varies in level. Values such as justice, social responsibility, and caring have begun to be taught, although the integration of Islamic teachings in PKN materials can still be improved. The challenges faced include limited curriculum, supporting resources, and pedagogical understanding of teachers. However, the integration of Islamic values has proven to be effective in improving students' character, such as tolerance and a sense of social responsibility. To optimize this implementation, curriculum development, improvement of teacher competence, diverse learning methods, and support for the school environment are needed. Collaboration between schools, parents, and the community is also important in strengthening the application of Islamic values